2009
DOI: 10.1038/jid.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Dendritic Cells from Human Cutaneous Squamous Cell Carcinoma Are Poor Stimulators of T-Cell Proliferation

Abstract: In order to determine the phenotype and function of myeloid DCs from human cutaneous squamous cell carcinoma (SCC), we studied their surface marker expression and allo-stimulatory potential ex vivo. There were abundant CD11c+ myeloid DCs, as well as TNF and inducible nitric oxide synthase (iNOS)-producing DCs (TIP-DCs), in and around SCC tumor nests. Although myeloid DCs from SCC, adjacent non-tumor bearing skin, and normal skin, were phenotypically similar by flow cytometry, and there was a pronounced genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 57 publications
8
86
2
2
Order By: Relevance
“…CSA has also been associated with the promotion of fibroblast proliferation (15). Past studies in SCID mice have supported a role of TGF-β in immune evasion by SCC; our early work supports a role for TGF-β in SCC development (26,27). The current study sheds light on potential mechanisms for CSA-induced SCC in transplant patients utilizing tissue from catastrophic patients in our cohort.…”
Section: Discussionmentioning
confidence: 79%
“…CSA has also been associated with the promotion of fibroblast proliferation (15). Past studies in SCID mice have supported a role of TGF-β in immune evasion by SCC; our early work supports a role for TGF-β in SCC development (26,27). The current study sheds light on potential mechanisms for CSA-induced SCC in transplant patients utilizing tissue from catastrophic patients in our cohort.…”
Section: Discussionmentioning
confidence: 79%
“…Accumulated evidence has also suggested that the emergence of tolerogenic DCs may be responsible for the development of tumor-mediated immune anergy (3,4). DCs isolated from animals and human cancer patients have phenotypic aberrations and functional loss (3,4). In addition, DCs located in the tumor's microenvironment not only inhibit T cell-based anticancer immune response, but promote the tumor's growth, and invasive and proangiogenic abilities (5)(6)(7).…”
mentioning
confidence: 99%
“…Dendritic cells (DCs) play pivotal roles in initiating innate and adaptive immune responses, which are responsible for the induction of anticancer immune responses (2). Accumulated evidence has also suggested that the emergence of tolerogenic DCs may be responsible for the development of tumor-mediated immune anergy (3,4). DCs isolated from animals and human cancer patients have phenotypic aberrations and functional loss (3,4).…”
mentioning
confidence: 99%
“…This effect appears to rely upon proximity to the tumour core in cSCC, DCs from peritumoral skin were stronger stimulators of T-Cell proliferation compared to those more centrally located 21 The effective response of immune cell infiltration is reduced in invasive cSCC, and they are capable of evading the effective immune response through multiple mechanisms 22 .…”
Section: Inflammatory Infiltration Of Cancermentioning
confidence: 99%
“…Infiltration score (n = 0 (7), 1 (21), 2 (19), 3 (20) Infiltration score correlates strongly with chemokine expression One-Way ANOVA of increasing infiltration scoring correlated with the expression of IL-8…”
Section: Figure 11 Thickness Of Lesions According To Infiltration Scmentioning
confidence: 99%